IMPLEMENTASI PENYULUH AGAMA ISLAM DALAM PRAKTIK BIMBINGAN AGAMA KEPADA WANITA TUNA SUSILA - Ully Aulia Lutfia (Jurnal Bimbingan Penyuluhan Islam, 2022)
This research departs from the reality of the practice of Islamic guidance for female prostitutes. Female prostitute is a social problem that must be stopped. It is a social problem because, it contradicts the values, religious norms and cultures of the society. Religious guidance is one of the efforts in dealing with prostitutes